2003
DOI: 10.1007/s00221-003-1678-z
|View full text |Cite
|
Sign up to set email alerts
|

Properties of human motor units after prolonged activity at a constant firing rate

Abstract: The primary purpose of this study was to examine if there are changes in the intrinsic properties of spinal motoneurons after prolonged submaximal contractions. To do this, we assessed whether or not the synaptic drive to motoneurons needs to increase in order to maintain a constant firing rate of a motor unit. Recruitment of new units and an increase in total electromyographic (EMG) activity of the muscle of interest were taken as estimates of an increase in synaptic drive. Subjects were asked to maintain a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
65
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 27 publications
7
65
0
1
Order By: Relevance
“…The inability to observe substitution or rotation is suggested to result from their experimental protocols. For example, in the paper by Smith (1934), an effort to discharge the target motor unit was increased continuously, which maintained the activity of that unit, and recruited additional units, similar to the results reported in a recent study by Johnson et al (2004). Later studies that have claimed substitution and rotation to occur (Basmajian 1973;Fallentin et al 1993;Person 1974;Thomas et al 1978) have actually observed switching between motor units within a complex muscle when the subject switched tasks (Loeb 1985;Riek and Bawa 1992).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…The inability to observe substitution or rotation is suggested to result from their experimental protocols. For example, in the paper by Smith (1934), an effort to discharge the target motor unit was increased continuously, which maintained the activity of that unit, and recruited additional units, similar to the results reported in a recent study by Johnson et al (2004). Later studies that have claimed substitution and rotation to occur (Basmajian 1973;Fallentin et al 1993;Person 1974;Thomas et al 1978) have actually observed switching between motor units within a complex muscle when the subject switched tasks (Loeb 1985;Riek and Bawa 1992).…”
Section: Introductionsupporting
confidence: 79%
“…These observations suggest changes in the intrinsic properties of higher-threshold motoneurons that render them incapable of further discharge. It has also been shown that a motoneuron requires stronger synaptic input to maintain a constant firing rate (Johnson et al 2004). If synaptic input is not increased, the firing rate of a motoneuron first decreases (Enoka et al 1989) and then the motoneuron ceases to fire.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, when motoneurons are repetitively stimulated by sustained intracellular currents, many cells either reduce their discharge or stop firing (Kernell and Monster, 1982a,b;Spielmann et al, 1993;Sawczuk et al, 1997). Similarly, in humans, the synaptic drive necessary to maintain repetitive firing of single motor units increases during weak contractions (Johnson et al, 2004). Therefore, several mechanisms probably contribute to changes in motoneuron excitability observed during fatiguing contractions, and different mechanisms are likely to be more prominent at different times during a sustained contraction (Gandevia, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is often studied during maximal voluntary contractions (5, 6, 9). Nevertheless, it is also present during weak physical contraction (1,2,8,(10)(11)(12). Central fatigue secures rotation of motor units (13) and prevents hyperactivity of muscles (6).…”
mentioning
confidence: 99%
“…The force produced by muscles decreases in part because of the lack of glycogen (3) in the muscle and/or failures at the neuromuscular junctions (4). In addition to this well-described muscle fatigue, motor fatigue also involves an element originating in the CNS (5)(6)(7)(8). This "central fatigue" is characterized by a decreased ability to contract the muscle fibers adequately during a motor activity and is observed independently of the muscle fatigue (6).…”
mentioning
confidence: 99%